Human Need for Religion - Rulia Rahmawati; Badruzzaman M. Yunus (Gunung Djati Conference Series, 2021)
This study aims to discuss the human need for religion. This research method is qualitative through literature study, while the approach to data interpretation uses content analysis. The results and discussion of this study include the understanding of religion, the background of the need for humans to religion, the concept of fitrah in an Islamic perspective. This research concludes that humans who live in this world cannot stand alone. In the sense that humans need guidance, guidance and guidance in this life. Therefore, the human need for religion is very important in this life.